Education in the city of Karbala 1921-1939 (Journal of the College of Basic Education, 2022)
The city of Karbala is considered one of the most prestigious religious cities among the Arab and Islamic cities. multiple intellectual.For this reason, this modest research was marked with (Education in the city of Karbala 1921-1939), which was divided into several axes, dealing with religious education because the city of Karbala was the destination of thousands of students and men of jurisprudence and religion, from various Islamic countries, and the large number of religious schools in the city of Karbala Then we touched on the books that were spread in the city of Karbala to teach children to read and write, especially in the last Ottoman era.